Fatal yellow fever among captive non-human primates in southern Colombia, 2025 - Sanchez-Rojas, Ivan Camilo; Bonilla-Aldana, D. Katterine; Solarte-Jimenez, Catherin Lorena; Bonilla-Aldana, Jorge Luis; Belisario-Tovar, Marixa; Ortega-Gómez, Sidaly; Zambrano-Quenan, Vilma Marielis; Perafan-Gomez, Julian Camilo; Gomez-Ocampo, Carlos Hernan; Delgado-Cajigas, Mayerly; Rodriguez-Morales, Alfonso J. (Frontiers in Veterinary Science, 2025)
BackgroundYellow fever virus (YFV) remains a re-emerging zoonotic threat in South America. While epizootics in free-ranging Alouatta spp. are well-documented, little is known about YFV infection in other Neotropical non-human primates (NHPs), particularly in captive settings. Here, we report eight NHP fatalities associated with YFV occurring in early 2025, in the Colombian department of Putumayo, a known endemic area.Cases descriptionBetween February and May 2025, eight fatal YFV cases were confirmed via RT-PCR in four NHP genera—Cebus albifrons, Ateles fusciceps (IUCN-endangered), Lagothrix lagotricha (vulnerable), and Aotus spp.—housed at wildlife centers or found nearby. Clinical signs included jaundice, lethargy, dyspnea, and mucosal pallor. Gross pathology revealed multisystemic involvement, with frequent hepatic necrosis, myocarditis, pulmonary edema, and severe parasitism. Histopathological examination in three representative cases identified hallmark features of yellow fever hepatitis: midzonal to centrilobular necrosis, Councilman bodies, steatosis, and sinusoidal congestion. These findings confirm fulminant YFV infection in previously undocumented captive primate hosts.ConclusionThis report presents the first evidence of natural YFV infection in C. albifrons, A. fusciceps, and L. lagotricha under managed care conditions. The presence of YFV in endangered and vulnerable NHPs has critical implications for conservation and public health. Epizootic surveillance protocols must expand beyond Alouatta spp. to include a broader range of species and captive populations. Reinforced vector control, biosafety measures, and One Health-based interventions are urgently needed to prevent spillover and enhance preparedness for future outbreaks.